TI_GERICHTE 52.2009.324 vom 16. September 2010 , Esercizio delle professioni di ingegnere e di architetto - ammonimento disciplinare - TI Tribunale d'appello (2010)
Esercizio delle professioni di ingegnere e di architetto - ammonimento disciplinare